The emergency medical service has a crucial role to unravel the genetics of sudden cardiac arrest in young, out of hospital resuscitated patients: Interim data from the MAP-IT study. (November 2021) - Tiesmeier, Jens; Gaertner, Anna; Homm, Sören; Jakob, Thomas; Stanasiuk, Caroline; Bachmann-Mennenga, Bernd; Henzler, Dietrich; Grautoff, Steffen; Veit, Gunter; Hori, Erika; Kellner, Udo; Gummert, Jan F.; et al.
Abstract: Background: Genetics of sudden cardiac deaths (SCD) remains frequently undetected. Genetic analysis is recommended in undefined selected cases in the 2021 ERC-guideline. The emergency medical service and physicians (EMS) may play a pivotal role for unraveling SCD by saving biomaterial for later molecular autopsy. Since for high-throughput DNA-sequencing (NGS) high quality genomic DNA is needed. We investigated in a prospective proof-of-concept study the role of the EMS for the identification of genetic forms of SCDs in the young. Methods: We included patients aged 1–50 years with need for cardiopulmonary resuscitation attempts (CPR). Cases with non-natural deaths were excluded. In two German counties with 562, 904 residents 39, 506 services were analysed. Paired end panel-sequencing was performed, and variants were classified according to guidelines of the American College of Medical Genetics (ACMG). Results: 769 CPR-attempts were recorded (1.95% of all EMS-services; CPR-incidence 68/100, 000). In 103 cases CPR were performed in patients < 50y. 58% died on scene, 26% were discharged from hospital. 24 subjects were included for genotyping. Of these 33% died on scene, 37.5% were discharged from hospital. 25% of the genotyped patients were carriers of (likely) pathogenic (ACMG-4/-5) variants. 67% carried variants with unknown significance (ACMG-3). 2 of them had familial history for arrhythmogenic cardiomyopathy or had to be re-classified as ACMG-4 carriers due to whole exome sequencing. Conclusion: The EMS contributes especially in fatal OHCA-cases to increase the yield of identified genetic conditions by collecting a blood sample on scene. Thus, the EMS can contribute significantly to primary and secondary prophylaxis in affected families.